A Bayesian Approach to Explore Risk Factors for Respiratory Dysfunction in Intensive Care Unit Patient - Shah N.B.N.H.; Razak N.N.B.A.; Samah A.B.A.; Razak N.A.B.A.; Ramasamy A.; Suhaimi F.M.; Chase J.G. (Politeknik Negeri Padang, 2024)
Respiratory dysfunction and failure are common in the intensive care unit (ICU)